(untitled) (Swiss Medical Weekly, 2012)
QUESTIONS UNDER STUDY AND PRINCIPLES: Estimating glomerular filtration rate (GFR) in hospitalised patients with chronic kidney disease (CKD) is important for drug prescription but it remains a difficult task. The purpose of this study was to investigate the reliability of selected algorithms based on serum creatinine, cystatin C and beta-trace protein to estimate GFR and the potential added advantage of measuring muscle mass by bioimpedance. METHODS: In a prospective unselected group of patients hospitalised in a general internal medicine ward with CKD, GFR was evaluated using inulin clearance as the gold standard and the algorithms of Cockcroft, MDRD, Larsson (cystatin C), White (beta-trace) and MacDonald (creatinine and muscle mass by bioimpedance). RESULTS: 69 patients were included in the study. Median age (interquartile range) was 80 years (73–83); weight 74.7 kg (67.0–85.6), appendicular lean mass 19.1 kg (14.9–22.3), serum creatinine 126 μmol/l (100–149), cystatin C 1.45 mg/l (1.19–1.90), beta-trace protein 1.17 mg/l (0.99–1.53) and GFR measured by inulin 30.9 ml/min (22.0–43.3). The errors in the estimation of GFR and the area under the ROC curves (95% confidence interval) relative to inulin were respectively: Cockcroft 14.3 ml/min (5.55–23.2) and 0.68 (0.55–0.81), MDRD 16.3 ml/min (6.4–27.5) and 0.76 (0.64–0.87), Larsson 12.8 ml/min (4.50–25.3) and 0.82 (0.72–0.92), White 17.6 ml/min (11.5–31.5) and 0.75 (0.63–0.87), MacDonald 32.2 ml/min (13.9‒45.4) and 0.65 (0.52‒0.78). CONCLUSIONS: Currently used algorithms overestimate GFR in hospitalised patients with CKD. As a consequence eGFR targeted prescriptions of renal-cleared drugs, might expose patients to overdosing. The best results were obtained with the Larsson algorithm. The determination of muscle mass by bioimpedance did not provide significant contributions.